¿Por qué es importante relacionar a la Comunidad Andina con la descentralización territorial? (2020)
The purpose of this text is to justify the relationship between Andean integration and territorial decentralization as systems of administrative organization, while leaving aside the economic scenario in the analysis and focusing on the political and legal perspective. The preferred research methodology is qualitative, and uses the analytical research method. For this purpose, both phenomena are described from the existing theory on the subject. In analyzing the theoretical framework of the particular subject, it was possible to justify the relationship between the aforementioned systems of administrative organization.